2017
DOI: 10.1016/j.exer.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Myopic defocus in the evening is more effective at inhibiting eye growth than defocus in the morning: Effects on rhythms in axial length and choroid thickness in chicks

Abstract: Animal models have shown that myopic defocus is a potent inhibitor of ocular growth: brief (1–2 hours) daily periods of defocus are sufficient to counter the effects of much longer periods of hyperopic defocus, or emmetropic vision. While the variables of duration and frequency have been well-documented with regard to effect, we ask whether the efficacy of the exposures might also depend on the time of day that they are given. We also ask whether there are differential effects on the rhythms in axial length or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 22 publications
1
42
0
Order By: Relevance
“…The growth inhibition caused by defocus or deprivation at mid-day (or deprivation in the morning) was not associated with any consistent effect on the rhythms in axial length, either for phase or for amplitude. However, if we compare the data for the 2-hour hyperopic defocus group to that of eyes receiving 2 hours of myopic defocus at the same times (Nickla et al 2017); Table 2), some interesting similarities are revealed: first, both types of defocus at mid-day (growth inhibition for both) caused significant phase-delays relative to the rhythms in eyes exposed to evening defocus. Second, both types of defocus in the morning (myopic defocus at this time prevents the compensatory inhibition; hyperopic defocus stimulates growth) caused abnormal 6-hour oscillations.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The growth inhibition caused by defocus or deprivation at mid-day (or deprivation in the morning) was not associated with any consistent effect on the rhythms in axial length, either for phase or for amplitude. However, if we compare the data for the 2-hour hyperopic defocus group to that of eyes receiving 2 hours of myopic defocus at the same times (Nickla et al 2017); Table 2), some interesting similarities are revealed: first, both types of defocus at mid-day (growth inhibition for both) caused significant phase-delays relative to the rhythms in eyes exposed to evening defocus. Second, both types of defocus in the morning (myopic defocus at this time prevents the compensatory inhibition; hyperopic defocus stimulates growth) caused abnormal 6-hour oscillations.…”
Section: Discussionmentioning
confidence: 98%
“…We suspect that the small degree of myopic defocus presumably experienced upon removal of the lens or diffuser is the cause. It is known that the temporal integration of myopic defocus is rapid (Schmid and Wildsoet 1996; Zhu et al 2005), and also that the myopic defocus signal is more effective later in the day, evincing a diurnal sensitivity in the “integrator” (Nickla et al 2017). These facts would explain the finding that removing the lens or diffuser after 2 hours of defocus in the mid-day, or after 6 hours of defocus in the morning (removal would occur at 1 pm), would cause a growth inhibition, whereas the 2-hours of morning defocus after removal would not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum inhibitory effect of myopic defocus on longitudinal changes in eye growth was observed in the group exposed to defocus in the evening, suggesting that myopic defocus is more effective at inhibiting eye growth when induced in the evening. Two hours of myopic defocus in the evening led to a phase advance (~4 hours) and an increase in the amplitude of axial length changes compared to the fellow control eye, which resulted in a similar hyperopic end point as full-time myopic defocus (Nickla et al, 2017b). Nickla and colleagues (2017a) also assessed the effects of 2 hours of hyperopic defocus imposed at different times of the day (morning and noon) upon eye growth and found that hyperopic defocus stimulated eye growth when imposed in the morning, but inhibited eye growth when imposed at noon.…”
Section: Diurnal Ocular Variationsmentioning
confidence: 93%
“…Nickla et al (2017b) examined the influence of a brief period (2 hours) of myopic defocus imposed at different times of the day (morning, noon and evening) upon the diurnal variations and the longitudinal changes (7 days) in axial eye growth of chicks. The maximum inhibitory effect of myopic defocus on longitudinal changes in eye growth was observed in the group exposed to defocus in the evening, suggesting that myopic defocus is more effective at inhibiting eye growth when induced in the evening.…”
Section: Diurnal Ocular Variationsmentioning
confidence: 99%